2008
DOI: 10.1002/iub.122
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics of lipid signaling: Protein kinase C as a paradigm

Abstract: SummaryThe lipid second messenger diacylglycerol (DAG) controls the rate, amplitude, duration, and location of protein kinase C (PKC) activity in the cell. There are three classes of PKC isozymes and, of these, the conventional and novel isozymes are acutely controlled by DAG. The kinetics of DAG production at various intracellular membranes, the intrinsic affinity of specific isoforms for DAG-containing membranes, the coordinated use of additional membrane-binding modules, the intramolecular regulation of DAG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 51 publications
0
67
0
Order By: Relevance
“…The latter observation was intriguing and suggested that these mutants may have an intrinsically higher affinity for a different membrane, notably Golgi, the preferred binding surface for PKC isozymes that do not use the C2 domain for membrane interactions (11). Thus, we assessed how these mutations affected Golgi translocation by targeting CFP to the Golgi using the N-terminal 33 amino acids of endothelial nitric-oxide synthase and monitoring translocation of YFP-PKC␣ to this membrane (11). Fig.…”
Section: Mutations In the C2 Domain Of Pkc␣ Alter Membrane Translocatmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter observation was intriguing and suggested that these mutants may have an intrinsically higher affinity for a different membrane, notably Golgi, the preferred binding surface for PKC isozymes that do not use the C2 domain for membrane interactions (11). Thus, we assessed how these mutations affected Golgi translocation by targeting CFP to the Golgi using the N-terminal 33 amino acids of endothelial nitric-oxide synthase and monitoring translocation of YFP-PKC␣ to this membrane (11). Fig.…”
Section: Mutations In the C2 Domain Of Pkc␣ Alter Membrane Translocatmentioning
confidence: 99%
“…Membrane binding acutely controls the amplitude of agonist-dependent signaling by conventional PKC isozymes (11). Live cell imaging studies using genetically encoded reporters to monitor PKC activity have revealed that signals that result in hydrolysis of phosphatidylinositol 4,5-bisphosphate result in two phases of conventional PKC activation: a rapid rise in activity that tracks with the rise in intracellular Ca 2ϩ (t1 ⁄ 2 of seconds) followed by slow decay in activity that tracks with the decay in diacylglycerol (t1 ⁄ 2 on the order of minutes at the plasma membrane and tens of minutes at the Golgi) (12).…”
mentioning
confidence: 99%
“…In the absence of phosphorylation at one or more of these sites, catalytic activation of these isoforms is impaired or enzyme stability is compromised. A model has therefore been proposed for PKC phosphorylation [14,85] in which (a) the primary translation product is phosphorylated at the A-loop by PDK-1 at the plasma membrane shortly after synthesis (b) PDK-1 disassociates from PKC, which is then followed by phosphorylation at the TM and HM sites via mTORC1/mTORC2-dependent pathways or autophosphorylation (c) these phosphorylations allow PKC to adopt a stable and 'closed' enzyme conformation in which the pseudosubstrate occupies the substrate-binding site and the enzyme predominantly localises to the cytosol. The enzyme is now in an inactive but signalling-competent state that is ready to be activated by lipid second messengers such as DAG.…”
Section: Pkc Phosphorylation: Constitutive or Inducible?mentioning
confidence: 99%
“…Residue Thr 538 has been described as critical for PKC catalytic activity for regulating phosphorylation of the hydrophobic motif and for enabling CD3-mediated nuclear factor-B (NF-B) activation (6). PKC also shows the unique property of being translocated to the plasma membrane lipid rafts during the immunological synapse between T cells and antigen-presenting cells (7)(8)(9). Recruitment of PKC to the immunological synapse induces the activation of intracellular signaling pathways as the mitogen-activated protein kinase and the NF-B pathway (10), essential for the regulation of T cell growth-promoting genes as IL-2 (interleukin-2) (3,11).…”
mentioning
confidence: 99%